Particle size control method of anti-corrosion doped polyaniline

Through dry high-frequency vibration friction treatment and wet film forming coating technology, the problems of doped polyaniline agglomeration and excessive particle size for anticorrosion are solved, and its efficient anticorrosion effect and storage stability in the coating film are achieved. , has promoted its industrial application in the field of anti-corrosion.

CN119463221AInactive Publication Date: 2025-02-18HUNAN YADA FENGHUI NEW MATERIAL CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202510047329.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-13
Publication Date
2025-02-18
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The existing doped polyaniline for anti-corrosion is prone to agglomeration in natural environments. The particle size is too large, so it cannot maximize the anti-corrosion effect in the coating film, and the storage stability is poor, which limits its industrial promotion.

Method used

Dry high-frequency vibration friction treatment and wet film forming coating technology are adopted to control the particle size of hydrochloric acid-doped polyaniline through pretreatment and dry friction treatment, and to improve its storage stability through wet film forming coating treatment.

Benefits of technology

It effectively solves the agglomeration problem of doped polyaniline, improves its anti-corrosion effect in coating films, and extends storage stability, promoting its application in the field of anti-corrosion.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119463221A_ABST
    Figure CN119463221A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of particle size control, and discloses a particle size control method of doped polyaniline for corrosion prevention, which comprises the following steps: (1) pretreating hydrochloric acid doped polyaniline, carrying out dry-method high-frequency vibration friction treatment on the pretreated hydrochloric acid doped polyaniline, carrying out particle size detection on the obtained powder, and after the obtained powder is qualified, carrying out dry-method high-frequency vibration friction treatment on the powder; the anti-corrosion doped polyaniline is obtained; and (2) carrying out wet-process film-forming coating treatment on a film-forming substance and the anti-corrosion doped polyaniline to obtain a finished product. According to the method provided by the invention, dry-process high-frequency vibration friction and wet-process film-forming coating are adopted, so that the problem of agglomeration of the doped polyaniline for corrosion prevention can be effectively solved, the situation that the polyaniline corrosion prevention effect cannot be shown to the greatest extent in later-stage film coating due to overlarge particle size of the material is avoided, and the application process of the polyaniline material in the corrosion prevention field is accelerated and promoted.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of particle size control, and in particular to a method for controlling the particle size of doped polyaniline for corrosion prevention. Background Art

[0002] As an electrically active polymer material, polyaniline's electrical activity originates from the P electron conjugated structure in the molecular chain: as the P electron system in the molecular chain expands, the P bonding state and antibonding state form the valence band and conduction band respectively. This non-localized P electron conjugated structure can form P-type and N-type conductive states after doping. Different from the doping mechanism of other conductive polymers that produce cationic vacancies under the action of oxidants, the number of electrons in polyaniline does not change during the doping process, but the doped proton acid decomposes to produce H + and counter anions (such as Cl - , sulfate, phosphate, etc.) enter the main chain and combine with the N atoms in the amine and imine groups to form polar and dipole delocalized to the P bond of the entire molecular chain, so that polyaniline has a higher conductivity. Anti-corrosion doped polyaniline has a high electrical activity. Its powder raw materials are very easy to agglomerate in the natural environment and cannot be used normally in the industrial production of coatings. Conventional wet grinding cannot effectively solve the problem.

[0003] At present, most of the doped polyaniline for corrosion prevention on the market has poor storage stability. The storage period in a vacuum, dry and cool environment (temperature 21±3℃, relative humidity 50±10%) generally does not exceed 2 months, which restricts the industrial promotion of doped polyaniline for corrosion prevention. Summary of the invention

[0004] The purpose of the present invention is to solve the problem of agglomeration of the existing anti-corrosion doped polyaniline and to overcome the defect that the anti-corrosion effect of the polyaniline cannot be maximized in the subsequent coating due to the excessively large particle size of the material.

[0005] In order to achieve the above object, the first aspect of the present invention provides a method for controlling the particle size of doped polyaniline for corrosion prevention, the method comprising the following steps: (1) pre-treating the hydrochloric acid doped polyaniline, and subjecting the pre-treated hydrochloric acid doped polyaniline to dry high-frequency vibration friction treatment, and testing the particle size of the obtained powder, and obtaining the anti-corrosion doped polyaniline after passing the test; (2) The film-forming material and the anti-corrosion doped polyaniline are subjected to a wet film-forming coating treatment to obtain a finished product.

[0006] The method provided by the present invention also has at least the following beneficial effects: The method provided by the present invention is to effectively solve the agglomeration problem of doped polyaniline for corrosion protection by adopting dry high-frequency vibration friction and wet film-forming coating, avoid the failure to maximize the anti-corrosion effect of polyaniline in the later coating due to excessively large material particle size, and accelerate the application process of polyaniline materials in the field of corrosion protection. BRIEF DESCRIPTION OF THE DRAWINGS

[0007] Figure 1 is a graph showing the initial particle size distribution of hydrochloric acid-doped polyaniline before pretreatment in step (1) of Example 1 of the present invention; Figure 2 is a particle size distribution diagram of the anticorrosion doped polyaniline obtained in step (1) of comparative example 1; Figure 3 is a particle size distribution diagram of the anti-corrosion doped polyaniline obtained in step (1) of Example 1 of the present invention; Figure 4 This is a particle size distribution diagram of the finished product obtained in step (2) of Example 1 of the present invention. DETAILED DESCRIPTION

[0008] The endpoints and any values ​​of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.

[0009] As mentioned above, the first aspect of the present invention provides a method for controlling the particle size of doped polyaniline for corrosion prevention, the method comprising the following steps: (1) pre-treating the hydrochloric acid doped polyaniline, and subjecting the pre-treated hydrochloric acid doped polyaniline to dry high-frequency vibration friction treatment, and testing the particle size of the obtained powder, and obtaining the anti-corrosion doped polyaniline after passing the test; (2) performing a wet film-forming coating treatment on the film-forming substance and the anti-corrosion doped polyaniline to obtain a finished product; In step (1), the pretreatment includes water washing, vacuum filtration, drying, and vacuum packaging for treatment in sequence; the water washing is to wash the hydrochloric acid-doped polyaniline in a deionized water tank by ultrasonic vibration for 30 minutes; the vacuum filtration is to remove water by vacuum filtration, and the drying is to spread it in a drying room and stand it at 40°C for 24 hours; In step (1), the conditions of the dry high-frequency vibration friction treatment are as follows: the grinding chamber capacity is 20L, the vibration mode is a fixed frequency 120 Hz vibration or a programmable 120-180 Hz vibration; In step (2), the film-forming substance includes: liquid epoxy resin and dispersant; the liquid epoxy resin is Baling Petrochemical E44 epoxy resin.

[0010] Preferably, in step (1), the conditions of the dry high-frequency vibration friction treatment meet the following requirements: zirconium dioxide beads or aluminum alloy rods are used as abrasives, and the filling volume of the abrasives is 12L.

[0011] In the present invention, in the dry high-frequency vibration friction treatment process, the abrasive is an important technical feature. The inventor of the present invention found in the experimental process that the hardness and wear resistance of zirconium dioxide zirconium beads or aluminum alloy rods are better.

[0012] More preferably, in step (1), the conditions of the dry high-frequency vibration friction treatment meet the following requirements: -25°C chilled water circulation cooling is used to control the inner cavity temperature to 5-10°C; and the grinding time is 2h.

[0013] Preferably, in step (1), the hydrochloric acid is doped with polyaniline, and the doping rate of the hydrochloric acid is 20-40 wt % based on polymethyl methacrylate.

[0014] In the present invention, the doping rate of hydrochloric acid in the hydrochloric acid-doped polyaniline is an important technical feature. The inventors of the present invention found in the experimental process that when the doping rate of the hydrochloric acid is 20-40wt%, it can provide a more efficient passivation layer conversion when the coating film contacts most metal substrates.

[0015] Preferably, in step (2), based on the total weight of the finished product, the amount of the liquid epoxy resin is 50-60wt%, the amount of the dispersant is 2-5wt%, and the amount of the anti-corrosion doped polyaniline is 38-50wt%.

[0016] Preferably, in step (2), based on the total weight of the finished product, the amount of the liquid epoxy resin is 52-58 wt%, and the amount of the anti-corrosion doped polyaniline is 38-45 wt%.

[0017] More preferably, in step (2), based on the total weight of the finished product, the amount of the liquid epoxy resin is 54-56 wt %, and the amount of the anti-corrosion doped polyaniline is 40-43 wt %.

[0018] Further preferably, in step (2), the conditions of the wet film-forming coating treatment meet the following requirements: the rotation speed is 1400-1600 r / min and the time is 1-2 h.

[0019] The present invention will be described in detail below by way of examples. In the following examples, unless otherwise specified, the raw materials are all commercially available.

[0020] In the following examples, unless otherwise specified, the hydrochloric acid-doped polyaniline was pretreated and then subjected to dry high-frequency vibration friction treatment within 30 days.

[0021] In the following examples, unless otherwise specified, the dispersant was purchased from BYK, Germany, with the brand number BYK-163.

[0022] In the following examples, unless otherwise specified, hydrochloric acid is doped with polyaniline, and the doping rate of hydrochloric acid is 38 wt % based on polymethyl methacrylate.

[0023] In the following examples, unless otherwise specified, “testing the fineness of the finished product, packaging and discharging the product; and performing storage stability testing” are performed in accordance with GB 1724-1979 “Determination of Fineness of Coatings” and GB 6753.3 “Testing Method for Storage Stability of Coatings”.

[0024] Embodiment 1: This example is used to provide a method for controlling the particle size of doped polyaniline for corrosion prevention, and the method includes the following steps: (1) pre-treating hydrochloric acid-doped polyaniline, taking 3 kg of the pre-treated hydrochloric acid-doped polyaniline, and subjecting it to dry high-frequency vibration friction treatment, and detecting and recording the particle size of the obtained powder to obtain anti-corrosion doped polyaniline; The pretreatment includes water washing, vacuum filtration, drying, and vacuum packaging for treatment in sequence; the water washing is to wash the hydrochloric acid-doped polyaniline in a deionized water tank by ultrasonic vibration for 30 minutes; the vacuum filtration is to remove water by vacuum filtration, and the drying is to spread it in a drying room and stand it at 40°C for 24 hours; The conditions of the dry high-frequency vibration friction treatment are as follows: the grinding chamber capacity is 20L, the vibration frequency is programmable at 120-180Hz (10min / cycle); zirconium dioxide zirconium beads are used as abrasives, and the filling volume of the abrasives is 12L; -25°C chilled water circulation cooling is used to control the inner chamber temperature to 5-10°C; the grinding time is 2h; (2) Performing wet film-forming coating treatment on the film-forming material and the anti-corrosion doped polyaniline, testing the fineness of the finished product, and packaging the product; and performing storage stability testing to evaluate the comprehensive stability after the treatment by the technology of the present invention; the film-forming material includes: Baling Petrochemical E44 epoxy resin and dispersant; Based on the total weight of the finished product, the amount of the Baling Petrochemical E44 epoxy resin used is 0.55 kg, the amount of the dispersant used is 0.04 kg, and the amount of the anti-corrosion doped polyaniline used is 0.41 kg; The wet film-forming coating treatment is carried out in a disperser, and the conditions of the wet film-forming coating treatment meet: a rotation speed of 1500 r / min and a time of 1 hour.

[0025] Embodiment 2: This example is carried out according to the method of Example 1, except that in step (2), based on the total weight of the finished product, the amount of the Baling Petrochemical E44 epoxy resin used is 0.52 kg, and the amount of the anti-corrosion doped polyaniline used is 0.45 kg. The remaining steps and parameters are the same as in Example 1.

[0026] Embodiment 3: This example is carried out according to the method of Example 1, except that in step (2), based on the total weight of the obtained finished product, the amount of the Baling Petrochemical E44 epoxy resin used is 0.58 kg, the amount of the anti-corrosion doped polyaniline used is 0.38 kg, and the remaining steps and parameters are the same as in Example 1.

[0027] Embodiment 4: This example is carried out according to the method of Example 1, except that in step (1), the hydrochloric acid is doped with polyaniline, based on polymethyl methacrylate, and the doping rate of hydrochloric acid is 20wt%. The remaining steps and parameters are the same as those of Example 1.

[0028] Embodiment 5: This example is carried out according to the method of Example 1, except that in step (1), an aluminum alloy rod is used as an abrasive in the dry high-frequency vibration friction treatment, and the remaining steps and parameters are the same as those of Example 1.

[0029] Embodiment 6: This example is carried out according to the method of Example 1, except that in step (1), the vibration mode used in the dry high-frequency vibration friction treatment is a fixed frequency of 120 Hz, and the remaining steps and parameters are the same as in Example 1.

[0030] Comparative Example 1: This example is used to provide a method for controlling the particle size of doped polyaniline for corrosion prevention, and the method includes the following steps: (1) pre-treating hydrochloric acid-doped polyaniline, taking 3 kg of the pre-treated hydrochloric acid-doped polyaniline, and subjecting it to dry high-frequency vibration friction treatment, and detecting and recording the particle size of the obtained powder to obtain anti-corrosion doped polyaniline; The pretreatment includes water washing, vacuum filtration, drying, and vacuum packaging for treatment in sequence; the water washing is to wash the hydrochloric acid-doped polyaniline in a deionized water tank by ultrasonic vibration for 30 minutes; the vacuum filtration is to remove water by vacuum filtration, and the drying is to spread it in a drying room and stand it at 40°C for 24 hours; The conditions of the dry high-frequency vibration friction treatment are as follows: the grinding chamber capacity is 20L, the fixed frequency is 150 Hz vibration; 304 stainless steel rods are used as abrasives, and the filling volume of the abrasives is 12L; -25°C chilled water circulation cooling is used to control the inner chamber temperature to 5-10°C; the grinding time is 2h; (2) Performing wet film-forming coating treatment on the film-forming material and the anti-corrosion doped polyaniline, testing the fineness of the finished product, and packaging the product; and performing storage stability testing to evaluate the comprehensive stability after the treatment by the technology of the present invention; the film-forming material includes: Baling Petrochemical E44 epoxy resin and dispersant; Based on the total weight of the finished product, the amount of the Baling Petrochemical E44 epoxy resin is 0.55 kg, the amount of the BYK-163 modified polyurethane solution wetting and dispersing agent is 0.04 kg, and the amount of the anti-corrosion doped polyaniline is 0.41 kg; The wet film-forming coating treatment is carried out in a disperser, and the conditions of the wet film-forming coating treatment meet: a rotation speed of 1500 r / min and a time of 1 hour.

[0031] Comparative Example 2: This example is used to provide a method for controlling the particle size of doped polyaniline for corrosion prevention, and the method includes the following steps: (1) pre-treating hydrochloric acid-doped polyaniline, taking 3 kg of the pre-treated hydrochloric acid-doped polyaniline, and subjecting it to dry high-frequency vibration friction treatment, and detecting and recording the particle size of the obtained powder to obtain anti-corrosion doped polyaniline; The pretreatment includes water washing, vacuum filtration, drying, and vacuum packaging for treatment in sequence; the water washing is to wash the hydrochloric acid-doped polyaniline in a deionized water tank by ultrasonic vibration for 30 minutes; the vacuum filtration is to remove water by vacuum filtration, and the drying is to spread it in a drying room and stand it at 40°C for 24 hours; The conditions of the dry high-frequency vibration friction treatment are as follows: the grinding chamber capacity is 20L, the fixed frequency is 150 Hz vibration; zirconium dioxide zirconium beads are used as abrasives, and the filling volume of the abrasives is 12L; -25°C chilled water circulation cooling is used to control the inner chamber temperature to 5~10°C; the grinding time is 2h; (2) Performing wet film-forming coating treatment on the film-forming material and the anti-corrosion doped polyaniline, testing the fineness of the finished product, and packaging the product; and performing storage stability testing to evaluate the comprehensive stability after the treatment by the technology of the present invention; the film-forming material includes: Baling Petrochemical E44 epoxy resin and dispersant; Based on the total weight of the finished product, the amount of the Baling Petrochemical E44 epoxy resin used is 0.55 kg, the amount of the dispersant used is 0.04 kg, and the amount of the anti-corrosion doped polyaniline used is 0.41 kg; The wet film-forming coating treatment is carried out in a disperser, and the conditions of the wet film-forming coating treatment meet: a rotation speed of 1500 r / min and a time of 1 hour.

[0032] Comparative Example 3: This example is used to provide a method for controlling the particle size of doped polyaniline for corrosion prevention, and the method includes the following steps: (1) pre-treating hydrochloric acid-doped polyaniline, taking 3 kg of the pre-treated hydrochloric acid-doped polyaniline, and subjecting it to dry high-frequency vibration friction treatment, and detecting and recording the particle size of the obtained powder to obtain anti-corrosion doped polyaniline; The pretreatment includes water washing, vacuum filtration, drying, and vacuum packaging for treatment in sequence; the water washing is to wash the hydrochloric acid-doped polyaniline in a deionized water tank by ultrasonic vibration for 30 minutes; the vacuum filtration is to remove water by vacuum filtration, and the drying is to spread it in a drying room and stand it at 40°C for 24 hours; The conditions of the dry high-frequency vibration friction treatment are as follows: the grinding chamber capacity is 20L, the vibration frequency is programmable at 120-180Hz (10min / cycle); 304 stainless steel rods are used as abrasives, and the filling volume of the abrasives is 12L; -25°C chilled water circulation cooling is used to control the inner chamber temperature to 5-10°C; the grinding time is 2h; (2) Performing wet film-forming coating treatment on the film-forming material and the anti-corrosion doped polyaniline, testing the fineness of the finished product, and packaging the product; and performing storage stability testing to evaluate the comprehensive stability after the treatment by the technology of the present invention; the film-forming material includes: Baling Petrochemical E44 epoxy resin and dispersant; Based on the total weight of the finished product, the amount of the Baling Petrochemical E44 epoxy resin used is 0.55 kg, the amount of the dispersant used is 0.04 kg, and the amount of the anti-corrosion doped polyaniline used is 0.41 kg; The wet film-forming coating treatment is carried out in a disperser, and the conditions of the wet film-forming coating treatment meet: a rotation speed of 1500 r / min and a time of 1 hour.

[0033] Test example: The data of the above examples and comparative examples are summarized and the results are shown in Table 1.

[0034] In Table 1, "initial particle size" is the particle size of the finished product after the wet film-forming coating treatment in step (2) of each example; "scraper fineness after 7 days of freeze-thaw storage at -15°C" and "scraper fineness after 30 days of thermal stability storage at 50°C" are obtained by testing in accordance with GB 1724-1979 "Determination of coating fineness".

[0035] It can be seen from the results in Table 1 that the embodiment of the present invention has a good effect of stabilizing the particle size of hydrochloric acid-doped polyaniline, and preferably has a programmable 120-180 Hz vibration (10 min / cycle), abrasive zirconium dioxide zirconium beads (filling volume 12L), -25°C chilled water circulation cooling, and controls the inner cavity temperature to 5-10°C. In the wet film-forming coating treatment, based on the weight of the finished product, 55wt% of Baling Petrochemical E44 epoxy resin, 41wt% of hydrochloric acid-doped polyaniline, and 4wt% of dispersant are prepared, and dispersed at a speed of 1500r / min for 1h, which has an excellent effect of controlling the particle size of the doped state; the obtained finished product can be stably stored at room temperature, and the time can be extended to 1 year, which is conducive to the promotion of polyaniline in the anti-corrosion industry.

[0036] In order to more clearly illustrate the method of the present invention, the present invention Figure 1 The initial particle size distribution diagram of the hydrochloric acid-doped polyaniline before pretreatment in step (1) of Example 1 of the present invention is shown. Figure 2 The particle size distribution of the anticorrosion doped polyaniline obtained in step (1) of comparative example 1 is shown. Figure 3 The particle size distribution of the anticorrosion doped polyaniline obtained in step (1) of Example 1 of the present invention is shown. Figure 4 The particle size distribution diagram of the finished product obtained in step (2) of Example 1 of the present invention is shown.

[0037] Among them, Figure 1 It can be seen that the initial particle size of the hydrochloric acid-doped polyaniline before pretreatment in step (1) of Example 1 of the present invention is concentrated around 100 μm. Such a coarse particle size will cause the performance of the polyaniline to be seriously degraded, or even have a negative effect.

[0038] Depend on Figure 2 It can be seen that the particle size distribution of the anti-corrosion doped polyaniline obtained in Comparative Example 1 is mainly concentrated in the range of 10 to 100 μm.

[0039] Depend on Figure 3 It can be seen that the particle size distribution of the anti-corrosion doped polyaniline obtained by dry high-frequency vibration friction treatment in step (1) of Example 1 of the present invention is mainly concentrated in a particle size of about 10 μm.

[0040] Depend on Figure 4 It can be seen that the particle size distribution of the finished product obtained in step (2) of Example 1 of the present invention is that the main particle size is concentrated at around 10 μm.

[0041] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.

Claims

1. A method for controlling the particle size of doped polyaniline for corrosion protection, characterized in that: The method comprises the following steps: (1) pre-treating the hydrochloric acid doped polyaniline, and subjecting the pre-treated hydrochloric acid doped polyaniline to dry high-frequency vibration friction treatment, and testing the particle size of the obtained powder, and obtaining the anti-corrosion doped polyaniline after passing the test; (2) performing a wet film-forming coating treatment on the film-forming substance and the anti-corrosion doped polyaniline to obtain a finished product; In step (1), the pretreatment includes water washing, vacuum filtration, drying, and vacuum packaging for treatment in sequence; the water washing is to wash the hydrochloric acid-doped polyaniline in a deionized water tank by ultrasonic vibration for 30 minutes; the vacuum filtration is to remove water by vacuum filtration, and the drying is to spread it in a drying room and stand it at 40°C for 24 hours; In step (1), the conditions of the dry high-frequency vibration friction treatment are as follows: the grinding chamber capacity is 20L, the vibration mode is a fixed frequency 120 Hz vibration or a programmable 120-180 Hz vibration; In step (2), the film-forming substance includes: liquid epoxy resin and dispersant; the liquid epoxy resin is Baling Petrochemical E44 epoxy resin.

2. The method according to claim 1, characterized in that In step (1), the conditions of the dry high-frequency vibration friction treatment are as follows: zirconium dioxide beads or aluminum alloy rods are used as abrasives, and the filling volume of the abrasives is 12L.

3. The method according to claim 1 or 2, characterized in that: In step (1), the conditions of the dry high-frequency vibration friction treatment are as follows: -25°C chilled water circulation cooling is used to control the inner cavity temperature to 5-10°C; the grinding time is 2h.

4. The method according to claim 1, characterized in that: In step (1), the hydrochloric acid is doped with polyaniline, and the doping rate of the hydrochloric acid is 20-40 wt % based on polymethyl methacrylate.

5. The method according to claim 1, characterized in that In step (2), based on the total weight of the finished product, the amount of the liquid epoxy resin is 50-60wt%, the amount of the dispersant is 2-5wt%, and the amount of the anti-corrosion doped polyaniline is 38-50wt%.

6. The method according to claim 5, characterized in that In step (2), based on the total weight of the finished product, the amount of the liquid epoxy resin used is 52-58 wt%, and the amount of the anti-corrosion doped polyaniline used is 38-45 wt%.

7. The method according to claim 5 or 6, characterized in that: In step (2), based on the total weight of the finished product, the amount of the liquid epoxy resin used is 54-56 wt%, and the amount of the anti-corrosion doped polyaniline used is 40-43 wt%.

Citation Information

Patent Citations

  • Method for recovering and regenerating refused battery critical material

    CN101030663A

  • Method for mechanically modifying doping polyaniline powder by adopting ball grinder

    CN101130267A

  • Using ball mill to process to mechanical doping intrinsic state polyaniline method

    CN101143470A

  • Doped polyaniline-epoxy-zinc powder composite coating and preparation method thereof

    CN103555137A

  • High-performance water-based polyaniline anticorrosive coating material and preparation method and application thereof

    CN103897558A